Combretum xylocarpum (Combretaceae), a new liana species from China - Liang, Dan; Yuan, Lang-Xing; Wang, Rui-Jiang (Phytotaxa, 2022)
Combretum xylocarpum, a new species from China, is described and illustrated. It is similar to C. acuminatum in leaf shape, spike position, flower structure and hypanthium shape, but obviously different from it by its fewer secondary veins, pale whitish flower petals, ellipsoidal woody fruits with 4 rounded ridges. In addition, the pollen grains of the new species exhibit unique characters comparing to other congeneric allies. Its conservation status is assessed to be Least Concern, according to the IUCN Red List Criteria and Category.